COMPARISON BETWEEN THE PETRIFILM™ AND THE CONVENTIONAL METHODS FOR ENUMERATING AEROBIC BACTERIA AND E.COLI IN LOCALLY PRODUCED SOFT CHEESE IN BAGHDAD - Zina Saab khudhir; Drgham.H.Yousif; Najim Hadi Najim (Basrah Journal of Veterinary Research)
The main objectives of the present study were to compare the petrifilm TM Aerobic count plates (ACP) with conventional standard plate count (SPC) for enumerating aerobic bacteria and secondly to compare the petrifilm TM coliform count plates (CCP) with conventional coliform plate count (CPC) method for isolation and enumeration of E.coli in locally produced soft white cheese samples .A total of 60 samples of soft cheese (30 samples to each petrifilmTM and conventional methods) have been collected randomly at weekly intervals from different retail markets in Baghdad province and its surroundings during the period of 6 months from the December 2011 till the May 2012.All results of cultural characteristics and biochemical reactions of E.coli isolates were in accordance with the main features described in Bergeys Manual of determinative bacteriology .The laboratory studies of the cultural isolation revealed that 20 (66.6%) isolates of E.coli were isolated from 30 soft white cheese samples by the conventional direct plating (CPC) method while 24 (80%) isolates of E.coli were isolated from another 30soft cheese samples by using a new petrifilm TM technique. The detection limit for aerobic bacteria by the petrifilm TM technique versus the conventional direct plating were 16x109 cfu/g and 5x108 cfu/g respectively while the detection limit of E.coli by the petrifilm TM technique versus the conventional coliform plate count (CPC) were 22X106 cfu/g and 12x105 cfu/g respectively. Results obtained in this study revealed that the petrifilm TM technique has been recognized to be significantly (P